Changes in ferroelectric properties of 0.7PMN-0.3PT ceramic with compressive stress - M. Unruan (2018)
In this work, effects of compressive stress on the ferroelectric properties of 0.7PMN-0.3PT ceramics were investigated. The ceramics with the formula (0.7)Pb(Mg1/3Nb2/3O3-(0.3)PbTiO were prepared by a conventional mixed-oxide method. The ferroelectric properties under compressive stress were observed at stress up to 80 MPa using a compressometer in conjunction with a modified Sawyer-Tower circuit. The results showed that applied stress had a significant influence on the ferroelectric properties of 0.7PMN-0.3PT ceramics. Ferroelectric characteristics, i.e. the area of the ferroelectric hysteresis (P-E) loop, the saturation polarization (P sat), the remanent polarization (Pr) and loop squareness (Rsq), decreased with increasing compressive stress, while the coercive field (Ec) remained relatively constant. Stress-induced domain wall motion suppression and non-180°C ferroelectric domain switching processes are responsible for the changes observed. © 2008 Trans Tech Publications, Switzerland.